Gangs in practice: violence prevention, law enforcement, and the received idea of the “Gang” - Kennedy, David M. (The Oxford handbook of gangs and society, 2024)
Gang researchers have long paid careful attention to the scholarly definition of a “gang,” resulting in a rich literature on such definitions, their strengths and weaknesses, and their implications for scholarship and practice. Little such attention has been paid to what “gang” means outside scholarly circles, including to law enforcement, politicians, the media, and members of the public. That “received idea of the gang” has very real implications for how those sectors understand gangs, their contribution to crime and violence, and how they should be addressed. It can be illuminated from formal sources and inferred from the orientations and actions of key public actors. An initial attempt at that illumination is presented here, and critical contrasts with what is in fact known about gangs are highlighted.